Pengaturan Keuangan Desa Dan Pengelolaanya di Desa Merbaun Kecamatan Amarasi Barat Kabupaten Kupang - Baunsele, Gerson Alexander I; Stefanus, Kotan Y; Ratu Udju, Hernimus (Artemis Law Journal, 2023)
The law regulates village areas so that they can handle and control their administration. Behind it are government focused programs identified with decentralization and local independence. Law Number 23 of 2014 concerning Regional Government determines villages, the main problem formulation raised is as follows (1) How are village finances and their management regulated in Kupang Regency? (2) What are the factors inhibiting village financial management in Merbaun Village, West Amarasi District, Kupang Regency? This research method uses a normative juridical research method (nommative legal research method) which is carried out by examining library materials or mere secondary data. The results of the research show that the residents of Merbaun village already know the work system of the Tempel village government in financial management of the village income and expenditure budget (APBDesa). There is evidence that development in 2021 has been realized in accordance with the community's aspirations, which are prioritized. The most triggering factor is the inhibitor is the source of funds. This means that the sources of funds provided by the APBN, district administration, grants and others are not in accordance with the plans detailed by the Merbaun village government institutions. The Merbaun village government should apply the principle of transparency in every expenditure and purchase so that all activities related to village government administration can be accessed by the entire community.